PF.05 Advances in Trisomy 21 Screening in the West Midlands, 1995–2011. (26th April 2013) - Tonks, AM; Gornall, AS; Larkins, SA; Hamilton, S; Gardosi, JO
Abstract : Background: Screening for trisomy 21 (T21) in the West Midlands has evolved from double screening in 1995 to combined screening in 2011, with the perception of improved detection amongst the public and providers. Methods: Cases of T21 (n = 2, 608) were identified using a regional, population-based, multiple source anomaly register covering a birth cohort of 1, 140, 866 between 1995 and 2011. Regional data on invasive testing were available for the same period. Results: The total prevalence of T21 increased by approximately 50% from 18.2 to 27.5 per 10, 000 births over the study period. The proportion of cases with a prenatal karyotype was unchanged (annual trend c2 = 0.21, p = 0.65; 52.8% in 1995 and 52.0% in 2011. However, karyotyping was taking place earlier in pregnancy; median gestation at procedure 19 weeks (1995) to 13 weeks (2011). TOP rates following prenatal karyotyping were unchanged, and the live birth rate was increased Within the total population (affected and unaffected pregnancies), the rate of amniocentesis and CVS combined for T21 indications decreased by 76% (4.7% of births in 1995 to 1.1% in 2011). Conclusion: The time and effort to develop the T21 screening programme has resulted in safer pregnancies for unaffected cases. Mothers of affected pregnancies have seen no improvement in prenatal diagnosis. The combination of an increasing prevalence of T21 with no change in prenatal diagnosis nor TOP rates means the live birth prevalence continues to rise at the same pace.